AKTIVITAS ANTIOKSIDAN DAN KANDUNGAN FENOLIK TOTAL FRAKSI N-HEKSAN DAN KLOROFORM DAUN JERUK PURUT (Citrus hystrix) - Fadilah Qonitah; Ahwan Ahwan (As-Syifaa Jurnal Farmasi, 2019)
Free radicals can cause several diseases. Antioxidants are the compounds that can reduce free radicals in the human body. Kaffir lime leaves contain phenolic and flavonoids compounds which have antioxidant activity. This research aimed to evaluate the antioxidant activity and to determine total phenolic contents of fraction n-hexane and chloroform from kaffir lime leaves. The antioxidant activity was determined by radical scavenging assay using DPPH (2,2-diphenyl-1-picrylhydrazyl) radical. The total phenolic content was determined by the spectrophotometric method. The results showed that the antioxidant activity of chloroform fraction (IC50: 302.91 ± 0.28 µg / mL) was higher than the n-hexane fraction (IC50: 714,25±1,97 µg /mL),but the antioxidant activity was lower than vitamin C (IC50: 3,28 ±0,12 µg /mL). The total phenolic content of chloroform fraction (4.73±0,33% w/w EAG) was higher than the n-hexane fraction (3,18 ± 0,31% w/w EAG).